Gaya Retorika Dakwah Bang Aswan - hidayatullah, ilham hidayatullah; Suherdiana, Dadan; Sukayat, Tata (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to examine the rhetorical style of Ustad Asep Wawan Sopian in his sermons, focusing on diction, language style, and body movements. The research objectives include: 1) Determining the word choice (diction) used by Ustad Asep Wawan Sopian according to the audience, consisting of youth and elders. 2) Analyzing various language styles such as comparison, satire, emphasis, and contradiction used in delivering the material. 3) Identifying the unique characteristics of Ustad Asep Wawan Sopian, who frequently touches on the behavior of his congregation in daily life. The research method used is qualitative descriptive, focusing on collecting data in the form of words from observations, interviews, and documentation. The results show that Ustad Asep Wawan Sopian adjusts his word choice, diction, and body movements according to his audience, making the delivered material more easily accepted. This study indicates that a preaching approach tailored to the characteristics of the congregation can enhance the effectiveness of message delivery.